2023
DOI: 10.1007/s44254-023-00019-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anxiety and postoperative adverse events: a narrative overview

Abstract: Patients awaiting surgical procedures often experience obvious anxiety due to discomfort and uncertain events, which is one of the most common clinical manifestations in perioperative patients. Numerous studies have confirmed that preoperative anxiety is closely related to the occurrence of postoperative adverse events, such as insomnia, pain, nausea and vomiting and neurocognitive dysfunction. Appropriate intervention or treatment for preoperative anxiety may contribute to reducing the incidence of postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Nevertheless, conflicting findings have emerged in the literature, as certain studies have documented divergent outcomes; one set of studies has shown that reducing preoperative anxiety results in a reduction in postoperative pain, while another set of studies has observed no alteration in the postoperative pain response [26,29,30]. The variability in findings may be due to the lack of homogeneity in the populations studied with respect to gender, medical and psychological history, indication for the surgical procedure, and anesthetic management [31]. Hence, only a comprehensive, large-scale study capable of mitigating the influence of these confounding factors will have the capacity to provide a conclusive answer to this question [31].…”
Section: Risk Factors For Preoperative Anxietymentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, conflicting findings have emerged in the literature, as certain studies have documented divergent outcomes; one set of studies has shown that reducing preoperative anxiety results in a reduction in postoperative pain, while another set of studies has observed no alteration in the postoperative pain response [26,29,30]. The variability in findings may be due to the lack of homogeneity in the populations studied with respect to gender, medical and psychological history, indication for the surgical procedure, and anesthetic management [31]. Hence, only a comprehensive, large-scale study capable of mitigating the influence of these confounding factors will have the capacity to provide a conclusive answer to this question [31].…”
Section: Risk Factors For Preoperative Anxietymentioning
confidence: 99%
“…The variability in findings may be due to the lack of homogeneity in the populations studied with respect to gender, medical and psychological history, indication for the surgical procedure, and anesthetic management [31]. Hence, only a comprehensive, large-scale study capable of mitigating the influence of these confounding factors will have the capacity to provide a conclusive answer to this question [31].…”
Section: Risk Factors For Preoperative Anxietymentioning
confidence: 99%
See 3 more Smart Citations